Analisis Kualitatif Pola Makan Balita Stunting di Wilayah Kerja Puskesmas Parigi Kabupaten Muna Tahun 2025 - Wa Tina; Hartati Bahar; Fifi Nirmala G (Inovasi Kesehatan Global, 2026)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition characterized by height below the age standard. This study aims to analyze the dietary patterns of stunted toddlers in the Parigi Community Health Center, Muna Regency, in 2025. The study used a qualitative approach with a phenomenological design. Informants consisted of mothers who had stunted toddlers as key informants and Posyandu cadres as supporting informants selected by purposive sampling. Data collection was carried out through in-depth interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions with triangulation validity tests. The results showed that feeding practices for stunted toddlers were still not in accordance with recommendations. All informants had carried out Early Initiation of Breastfeeding (IMD), but exclusive breastfeeding was not optimal due to the perception of insufficient breast milk. Complementary breastfeeding (MP-ASI) tended to be given before the age of 6 months, influenced by the assumption that babies were hungry when they cried and cultural habits. The frequency of toddler meals was irregular, the type of food was dominated by porridge, and food variety was still limited. Consumption of animal side dishes, vegetables, and fruit was also not routinely provided. In conclusion, the dietary patterns of stunted toddlers in the study area do not meet the principles of balanced nutrition and are still influenced by family knowledge and habits. Therefore, increased education for mothers and families regarding appropriate feeding practices is needed to support optimal toddler growth and development.